Nationalism: A Politico-Aesthetic Study of Finnegans Wake - Sajila Karim Khan; Rasib Mehmood; Huma Ahmed (International Journal of Business and Economic Affairs, 2024)
This research investigates nationalism, especially concerning the Irish identity. Writer has set nationalist ideals in the background of humor, historical references, and complex storytelling. The novel questions the fixed narratives that nationalism often imposes. The novel’s narrative technique and stylistic innovation, mythic references, and looping timeline, invite readers into a world where identities constantly shift and blend. It examines the limitations of national identity and skepticism of the writer regarding national ideals. In light of politico-aesthetic discourse of thinkers like Jacques Rancière, Walter Benjamin, and Herbert Marcuse, this analysis reveals how the novel portrays nationalism as an endless cycle of pride and doubt. This dynamism shapes culture and opens up to reinterpretation and transformation.